Corporate governance and audit qualifications in sri lanka does corporate governance matter - Pratheepkanth, P. (University of Jaffna, 2020)
The aim of this study is to investigate the corporate governance role of external audits in Sri Lanka as an emerging market context. Using a sample of Sri Lankan firms, the paper uses regression analysis techniques to test the corporate governance (i.e., block ownership, family ownership, insider ownership, board size) and qualified opinion (indicating whether the firm receives qualified opinion). The empirical evidence indicates that ownership concentration (i.e., block ownership, family ownership, insider ownership) provides better corporate governance leading to higher quality financial reporting and therefore, less likelihood of receiving qualified audit reports. Whilst, board size is insignificantly positively related to audit qualifications implying that possibility of receiving an audit qualification. These findings provide Sri Lankan listed firms with an insight on how to improve/practice their financial reporting quality and audit mechanisms. These results can also serve as a useful reference for firms and the academics concerning future strategies and decision making.
Keywords: Corporate governance; Audit report; Audit qualification; Sri lanka